Presenting a model of influencing factors on improving the quality of urban transportation management (Scientific Journal of Research Studies in Future Management, 2023)
In the recent era, due to the expansion of urbanization and the increase of vehicles, the urban model and transportation management are very important in this field. Based on this, this research presented a model of factors influencing the quality improvement of urban transportation management. This was an exploratory descriptive research and its population was all experts, experts and managers and experts of the urban transportation sector, 385 of whom completed the researcher-made questionnaire in an accessible manner, which emphasized its psychometric features. The findings of the exploratory analysis in this field showed that according to the results of the exploratory factor analysis, 5 main factors can be identified among the 32 existing indicators. These factors were named based on the opinion of experts and based on the content analysis of the concepts of strategic management, location, infrastructure development, technology and innovation, and green management, and these factors explained 71% of the dispersion of urban transportation management quality.